Effect of ZnO-PCL nanocomposite thickness on attenuation in a rectangular waveguide at microwave frequency using FEM - Yakubu, Abubakar; Abbas, Zulkifly; Ibrahim, Nor Azowa (Taylor & Francis, 2015)
Presented in this work is an essential and basic approach to compute the attenuation of electromagnetic waves propagating through a rectangular waveguides with lossy material sample placed inside the waveguide. The rectangular waveguide (WR 90) technique is used to theoretically calculate the attenuation of electromagnetic wave as it interacts with ZnO-PCL nanocomposites of different sample thicknesses from measurements of transmission /reflection coefficients in the X-Band. Finite element method (FEM) was also used to calculate attenuation for the same sample thicknesses at X-Band. Comparison of the attenuation results obtained from experiment and FEM were analysed. Among other findings, it was found that the composite with 6.8 mm thickness gave the highest attenuation within the frequency range measured. The comparative study between the techniques showed close measurement system agreement. The value of attenuation for the different thicknesses measured showed that the composites is a good material for microwave low absorption. This material composites can be applied to mobile communication devices as thin layer circuit board for electromagnetic wave absorption.